Knowledge is power: harnessing clinical database for better informed laboratory medicine practice - Loh, Tze Ping (Journal of Laboratory and Precision Medicine, 2017)
There is a saying in the research community that if the world stops performing any laboratory-based research, it will still have enough data to be analysed over the next 5 years. The anecdote underscores two important issues that are at the heart of modern day research and is also applicable to laboratory medicine.